2018
DOI: 10.1155/2018/7270137
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐Structure Interaction Effect on Fragility Curve of 3D Models of Concrete Moment‐Resisting Buildings

Abstract: This paper presents the probabilistic generation of collapse fragility curves for evaluating the performance of 3D, reinforced concrete (RC) moment-resisting building models, considering soil-structure interaction (SSI) by concentration on seismic uncertainties. It considers collapse as the loss of lateral load-resisting capacity of the building structures due to severe ground shaking and consequent large interstory drifts intensified by -Δ effects as well as the strength and stiffness deterioration of their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Detrimental effects of SSI considering different soil a b Fig. 17 Seismic response of pipelines in terms of a PGA versus strain (ε), b PFA versus strain strain (ε) and c PGA versus PFA in decoupled case without SSI (ε y is the yield strain of the material) a b modelling for RC buildings have also been observed in Karapetrou et al (2015) and Anvarsamarin et al (2018). When it comes to CC (Fig.…”
Section: Structural Componentsmentioning
confidence: 94%
“…Detrimental effects of SSI considering different soil a b Fig. 17 Seismic response of pipelines in terms of a PGA versus strain (ε), b PFA versus strain strain (ε) and c PGA versus PFA in decoupled case without SSI (ε y is the yield strain of the material) a b modelling for RC buildings have also been observed in Karapetrou et al (2015) and Anvarsamarin et al (2018). When it comes to CC (Fig.…”
Section: Structural Componentsmentioning
confidence: 94%
“…As an extensive application, two more different earthquakes including the Cape Mendocino (magnitude 7.1, April 1992) and Landers (magnitude 7.4, June 1992) earthquake are considered. The horizontal components of the earthquakes (CAPEMEND/ RIO360 and LANDERS/YER270) (Anvarsamarin et al, 2018) are taken as the input for the parametric optimization. The sampling rate for these earthquakes is also 0.02 s. The total time is 36 and 44 s for Cape Mendocino and Landers earthquakes, respectively.…”
Section: Seismic Mitigation Case Studiesmentioning
confidence: 99%
“…Moon, et al [12] employed a fragility approach to investigate the effect of plan structural irregularity and confirmed that the more irregular the structures, the higher the risk they pose. Meanwhile, the effect of the soilstructure interaction on the fragility curves was investigated by Anvarsamarin, et al [13] with the finding that adopting the average spectral acceleration (S a.avg ) intensity measure is more efficient in capturing the effect of the inherent uncertainties of strong ground motions on the structural response parameters.…”
Section: Introductionmentioning
confidence: 99%